2019
DOI: 10.3390/cancers11050655
|View full text |Cite
|
Sign up to set email alerts
|

A Role for NF-κB in Organ Specific Cancer and Cancer Stem Cells

Abstract: Cancer stem cells (CSCs) account for tumor initiation, invasiveness, metastasis, and recurrence in a broad range of human cancers. Although being a key player in cancer development and progression by stimulating proliferation and metastasis and preventing apoptosis, the role of the transcription factor NF-κB in cancer stem cells is still underestimated. In the present review, we will evaluate the role of NF-κB in CSCs of glioblastoma multiforme, ovarian cancer, multiple myeloma, lung cancer, colon cancer, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 161 publications
(179 reference statements)
1
63
0
1
Order By: Relevance
“…NF-κB signaling is known to maintain the characteristics of CSCs associated with cancer progression. After cisplatin treatment, the dormant cells displayed an increased expression of cells with CSCs markers in OC, indicating the resistance of this cell fraction [ 39 ]. Targeting the PTGS2-NF-κB axis in CSCs will provide new insight into OC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB signaling is known to maintain the characteristics of CSCs associated with cancer progression. After cisplatin treatment, the dormant cells displayed an increased expression of cells with CSCs markers in OC, indicating the resistance of this cell fraction [ 39 ]. Targeting the PTGS2-NF-κB axis in CSCs will provide new insight into OC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 can be activated by receptor tyrosine kinases such as c-Met in a Janus family kinase-mediated way [25,43]. NF-κB is an ubiquitously expressed transcription factor and a key player in cancer initiation and progression by promoting proliferation of cancer cells and inhibiting cancer cells apoptosis [44]. Recently, it was found that c-Met can activate PI3K/Akt signaling pathway, leading to downstream activation of NF-κB to promote tumor metastasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although some established cellular model lines were derived from primary native tumor tissue [ 7 , 8 , 12 ], such cell lines still lack cancer stem cell characteristics. Cancer stem cells (CSC) are a small subpopulation of tumor cells of high plasticity driving tumor growth, repopulation after injury, and metastasis in a broad range of solid tumors including CRC [ 13 , 14 ]. Next to mediating invasiveness and resistance to chemotherapy, CSC also use immune system escape and are thus crucial mediators of cancer relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Next to mediating invasiveness and resistance to chemotherapy, CSC also use immune system escape and are thus crucial mediators of cancer relapse. Next to in vitro propagation as spheres [ 14 , 15 , 16 , 17 ], cancer stem cell markers like prominin-1 (CD133) and CD44 antigen (CD44) are frequently used to identify cancer stem cells in CRC [ 3 , 6 ]. Important regulators of cancer stem cell characteristics particularly include the members of the MYC transcription factor family, consisting of L-, N-, and CMYC.…”
Section: Introductionmentioning
confidence: 99%